Self-determination theory applied to Dark Souls: fostering motivation in video game communities - Váscones-Román, Fritz Fidel (2026)
Background: Video games have emerged as a significant field of study in psychology, particularly in understanding human motivation. Self-Determination Theory (SDT) posits that human motivation is driven by three basic psychological needs: autonomy, competence, and relatedness. Objective: To examine how the basic psychological needs outlined by Self-Determination Theory—autonomy, competence, and relatedness—are fulfilled through the design of Dark Souls and the interactions within its online communities. Method: This study employed an exploratory qualitative approach, utilizing content analysis of comments from Dark Souls-related subreddits. A total of 82 comments were analyzed, focusing on themes related to autonomy, competence, and relatedness. Ethical considerations were addressed by ensuring the anonymity of users and focusing on publicly available data. Result: The findings confirm and extend previous research on Self-Determination Theory, showing that Dark Souls uniquely fulfills the psychological needs of competence, autonomy, and relatedness. Its design, normalizing failure and rewarding perseverance, promotes intrinsic motivation and resilience, while online community interactions strengthen belonging and emotional support. These results suggest that challenging games combining meaningful choices with social engagement can foster both intrinsic motivation and emotional well-being, offering valuable insights for academic research and game design. Conclusion: This study reaffirms the relevance of Self-Determination Theory in explaining how challenging games like Dark Souls satisfy players’ basic psychological needs. Future research should examine how these dynamics operate in other gaming genres and cultural contexts and explore their application in educational and therapeutic settings.